Supporting adolescents with autism in secondary schools - Odom, Samuel L. (New York, NY The Guilford Press, 2023)
"The book discusses the Center on Secondary Education for Students with Autism (CSESA), which is designed to support all students with autism in high school, and the breadth of the learning needs for those autistic students is broad. For many of these students, four domains of emphasis are important: Transition and Families, Academics, Peer and Social Competence, and Personal Independence and Behavior. The CSESA program consists of specific component interventions and practices that address each of these domains, which are highlighted in the book chapters"--
Somewhere to go, something to do, someone to love : adolescents in high school and the CSESA comprehensive program / Samuel L. Odom & Kara A. Hume -- CSESA foundations / Samuel L. Odom -- Transition / Bonnie R. Kraemer, Sara McDaniel, Catherine Fowler & Tara Regan -- Academics/literacy / Christopher Brum, Laura J. Hall & Colleen Reutebuch -- Peer and social domain / Jessica Steinbrenner, Laura J. Hall, Erik W. Carter, and Janine Stichter -- Independence and behavior : PRomoting Independence & Self-Management (PRISM) / Kara Hume, Suzanne Kucharczyk, Lindsay Rentschler, & Brian Boyd -- Families / Leann DaWalt & Kate Szidon -- Implementation process / Laura J. Hall, Jessica Steinbrenner, Suzanne Kucharczyk, & Yolanda Perkins -- Research and evaluation / Kara Hume.
Includes bibliographical references and index.
Keywords: Center on Secondary Education for Students with Autism Spectrum Disorder; Autistic youth -- Education (Secondary) -- United States; Youth with autism spectrum disorders -- Education (Secondary) -- United States